2022
DOI: 10.4314/tjpr.v20i7.24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pesticide residues in vegetables from Mekong, Delta, Vietnam using LC-MS/MS

Abstract: Purpose: To assess the levels of pesticide residues in commonly used vegetables in Vietnam as a reference for future monitoring. Methods: A total of 180 samples of six different fresh vegetables including watercress, mustard green, choy sum, daikon, okra, and yam were analyzed from Mekong Delta, Vietnam. Ten popular pesticides were evaluated using liquid chromatography-tandem mass spectrometry (LC-MS/MS) after extraction with a multi-residue method (QuEChERS method). Results: The results were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…The percentage of MRL violation (13.3%) observed in the present work was higher as compared to other studies from Korea (1.4%) and Poland (1.8%) (Yu et al, 2018;Yi et al, 2020). On the contrary, Asian countries such as Vietnam (59%) and Thailand (24%) reported MRL violations at higher rates than those reported in the present work (Sapbamrer and Hongsibsong, 2014;Nguyen et al, 2021). Total samples > MRL 8 (13.3) ND = not detectable; and MRL = maximum residue limit.…”
Section: Frequency Of Detection and Exceedance Of Mrlcontrasting
confidence: 87%
“…The percentage of MRL violation (13.3%) observed in the present work was higher as compared to other studies from Korea (1.4%) and Poland (1.8%) (Yu et al, 2018;Yi et al, 2020). On the contrary, Asian countries such as Vietnam (59%) and Thailand (24%) reported MRL violations at higher rates than those reported in the present work (Sapbamrer and Hongsibsong, 2014;Nguyen et al, 2021). Total samples > MRL 8 (13.3) ND = not detectable; and MRL = maximum residue limit.…”
Section: Frequency Of Detection and Exceedance Of Mrlcontrasting
confidence: 87%
“…To control the safe and efficient use of pesticides, their residues are regularly monitored in food and environmental samples in many countries according to risk-based sampling plans [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] or targeted surveillance with limited scope and sampling targets. For example, the world-wide activities are demonstrated with some selected publications from Argentina to Vietnam [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In the European Union the largest number of residues tested within the EU-coordinated and national pesticide residue monitoring programs were reported in 2020 by Luxembourg (659), Malta (643), Germany (626), France (619) and Belgium (617) [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most publications referenced above [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] mainly reported minor modifications in sample preparation procedures of the original QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) method [ 52 ] and often provided details of the conditions of the MS mass spectrometry (MS) detection. Other authors reported various combinations of sample preparation [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%